An individualized functional magnetic resonance imaging protocol to assess semantic congruency effects on episodic memory in an aging multilingual population - Perquin, Magali; Viswanathan, Shivakumar; Vaillant, Michel; Risius, Okka; Huiart, Laetitia; Schmit, Jean-Claude; Diederich, Nico J.; Fink, Gereon R.; Kukolja, Juraj (Frontiers in Aging Neuroscience, 2022)
The cognitive stimulation induced by multilingualism may slow down age-related memory impairment. However, a suitable neuroscientific framework to assess the influence of multilingualism on age-related memory processes is missing. We propose an experimental paradigm that assesses the effects of semantic congruency on episodic memory using functional magnetic resonance imaging (fMRI). To this end, we modified the picture-word interference (PWI) task to be suitable for multilingual subjects undergoing functional magnetic resonance imaging (fMRI). In particular, stimulus material was prepared in multiple languages and closely matched in semantic properties, thus enabling participants to perform the experiment in a language of their choice. This paradigm was validated in a group (n = 62) of healthy older (>64 years) multilingual subjects, all practicing three or more languages. Consistent with the engagement of semantic congruency processes, we found that the encoding and recognition of semantically related vs. unrelated picture-word pairs evoked robust differences in behavior and the neural activity of parietal-temporal networks. These effects were not modulated by the language in which the task was performed. Based on this validation in a multilingual population, we conclude that the proposed paradigm will allow future studies to evaluate whether multilingualism aptitude engages neural systems in a manner that protects long-term memory from aging-related decline.